2014
DOI: 10.1371/journal.pbio.1001809
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Screen Reveals an Extensive Layer of Transcriptional and Splicing Control Underlying RAS/MAPK Signaling in Drosophila

Abstract: A global RNAi screening approach in Drosophila cells identifies a large group of transcription and splicing factors that modulate RAS/MAPK signaling by altering the expression of MAPK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 130 publications
7
73
1
1
Order By: Relevance
“…Biochemical studies indicate that Nito, like its human ortholog, copurify with the precatalytic spliceosome (complex B) (34). In addition, nito, as well as many other splicing factors, was identified in an RNAi screen for RAS/MAPK signaling components (35). Consistent with these findings, we find that nito is required for the alternative splicing of the master sex-determination gene Sxl.…”
Section: Discussionsupporting
confidence: 81%
“…Biochemical studies indicate that Nito, like its human ortholog, copurify with the precatalytic spliceosome (complex B) (34). In addition, nito, as well as many other splicing factors, was identified in an RNAi screen for RAS/MAPK signaling components (35). Consistent with these findings, we find that nito is required for the alternative splicing of the master sex-determination gene Sxl.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, we identified several splicing factors, including Prp19 and Prp8, in a genome-wide RNAi screen in S2 cells for modulators of Ras-induced MAPK activation (Ashton-Beaucage et al 2014). Incidentally, a single mutant allele of Prp8 was also recovered in the CCT screen (reported in Ashton-Beaucage et al 2014). Characterization of their implication in the pathway revealed that they specifically regulate MAPK protein levels by controlling the alternative splicing of selected introns of the mapk pre-mRNAs.…”
Section: Modifiers Of Dominant-negative Cnkmentioning
confidence: 99%
“…(B) Epistasis analysis in Drosophila S2 cells employing constitutively active forms of RAS, RAF, and MEK to induce MAPK activation [8]. Phosphorylated MAPK was measured by quantitative microscopy and normalized to a GFP dsRNA control [7].…”
Section: Introductionmentioning
confidence: 99%